Breastfeeding Practices among Young Mothers: A Scoping Reviews - Rokhmah, Nur Laeli; Astuti, Andari Wuri (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to evaluate the evidence related to breastfeeding practices among young mothers. The method of this scoping review used the Arksey & O'Malley framework which consists of 5 stages: Identifying review questions with the PICO framework; identifying of relevant studies; searching articles through relevant databases such as PubMed, Science Direct and Wiley; PRISMA Flow Chart was applied to describe the process of selecting articles transparently; conducting a critical appraisal to assess the quality of the articles; providing data charting; compiling, summarizing and reporting the results. Based on 10 articles included, there were 7 articles using qualitative methods, 2 using RCT and 1 using mix methods; 9 articles from developed countries and 1 article from LMIC. Furthermore, 4 themes were obtained, namely (1) The decision making process that is influenced by infant health reasons and support; (2) Factors affecting the success of breastfeeding practices, including young mothers' knowledge about the benefits of breastfeeding, perceived comfort of mothers in breastfeeding and relational support from professionals; (3) Obstacles in breastfeeding i.e. mothers have difficulty in giving breastfeeding, have demands for school time or work and stigma. (4) Needs of breastfeeding mothers, namely young mothers needing health care and support. It can be concluded that within LMIC show that young mothers tend to focus on breastfeeding practices and physical health issues because they have received support from the family. While within developed countries show that young mothers focus more on psychological problems.